2019
DOI: 10.1002/pat.4764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen plasma treatment on the crystallinity and self‐bonding of polyetheretherketone (PEEK) for biomedical applications

Abstract: Polyetheretherketone (PEEK) is a thermoplastic material with outstanding properties and high potential for biomedical applications, including hermetic encapsulation of active implantable devices. Different biomedical grade PEEK films with initial degree of crystallinity ranging from 8% to 32% (with or without mineral filling) were inspected. PEEK surfaces were treated with nitrogen RF plasma and the effects on materials crystallinity and self-bonding were evaluated. In particular, the relationship between auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…For example, Younis et al [ 120 ] showed that plasma treatment of nitrogen gas exerted a positive influence on the SBS of unfilled PEEK and veneering composites. Similar results after nitrogen gas plasma treatment were obtained by Fedel et al [ 124 ]. Therefore, plasma treatment was a suitable surface treatment to improve the bond strength of PEEK materials to dental composites.…”
Section: Adhesion Of Peek To Dental Compositessupporting
confidence: 90%
“…For example, Younis et al [ 120 ] showed that plasma treatment of nitrogen gas exerted a positive influence on the SBS of unfilled PEEK and veneering composites. Similar results after nitrogen gas plasma treatment were obtained by Fedel et al [ 124 ]. Therefore, plasma treatment was a suitable surface treatment to improve the bond strength of PEEK materials to dental composites.…”
Section: Adhesion Of Peek To Dental Compositessupporting
confidence: 90%
“…The changes in PEEK’s surface, induced this way, significantly enhanced mouse fibroblasts and human osteoblasts adhesion, proliferation, and also metabolic activity. Other studies exhibit that PEEK plasma treatment can considerably improve its adhesive features, which is very important when applying various organic or non-organic coatings [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This led to the enhancement of the adhesion and proliferation rate of human osteoblasts seeded on the PEEK surface. Other studies have shown that modifications of PEEK surfaces using low-temperature plasmas can significantly improve its adhesive properties which are very important when applying organic or non-organic coatings [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%